Isolation and characterization of virus of highly pathogenic avian influenza H5 subtype of chicken from outbreaks in Indonesia - Wiyono, Agus; Indriani, R; Dhamaryanti, N.L.P.I; Damayanti, R; Parede, L; Syafriati, T; ., Darminto (Indonesian Animal Sciences Society, 2004)
A study on the isolation and characterization of Highly Pathogenic Avian Influenza of chicken from outbreaks in Indonesia was conducted at Indonesian Research Institute for Veterinary Science. Outbreaks of avian disease had been reported in Indonesia since August 2003 affecting commercial layer, broiler, quail, and ostrich and also native chicken with showing clinical signs such as cyanosis of wattle and comb, nasal discharges and hypersalivation, subcutaneous ptechiae on foot and leg, diarre and sudden high mortality. The aim of this study is to isolate and characterize the causal agent of the disease. Samples of serum, feather follicle, tracheal swab, as well as organs of proventriculus, intestine, caecal tonsil, trachea and lungs were collected from infected animals. Serum samples were tested haemaglutination/haemaglutination inhibition to Newcastle Disease and Egg Drop Syndrome viruses. Isolation of virus of the causal agent of the outbreak was conducted from samples of feather follicle, tracheal swab, and organs using 11 days old specific pathogen free (SPF) embryonated eggs. The isolated viruses were then characterised by agar gel precipitation test using swine influenza reference antisera, by haemaglutination inhibition using H1 to H15 reference antisera, and by electron microscope examination. The pathogenicity of the viruses was confirmed by intravenous pathogenicity index test and its culture in Chicken Embryo Fibroblast primary cell culture without addition of trypsin. The study revealed that the causative agent of the outbreaks of avian disease in Indonesia was avian influenza H5 subtype virus based upon serological tests, virus isolation and characterization using swine influenza reference antisera, and electron microscope examination. While subtyping of the viruses using H1 to H15 reference antisera suggested that the virus is very likely to be an avian influenza H5N1 subtype virus. The pathogenicity test confirmed that the viruses are highly pathogenic to experimental animals. It is concluded that the causative agent of the outbreaks of avian disease in Indonesia was avian influenza H5 subtype virus. The result has been the basis of further study such as development serological tests and vaccine production. The decission of Indonesian Government to conduct vaccination program using homolog vaccine in order to control the disease is regarded as the correct choice. However, it should be accompanied by conducting surveillance and monitoring of the disease as well as the possibility of mutation of virus. The program should be coordinated nationally. Â Key words: Virus isolation, characterization, chicken, outbreak, highly pathogenic avian influenza (HPAI), H5 subtype, Indonesia